Consumers' Attitudes toward Ecological Packaging - Iga LAMAR (Communications of International Proceedings, 2021)
The main objective of this paper is to evaluate consumers’ attitudes toward ecological packaging. The research using the online questionnaire survey was conducted among 275 Polish respondents in July 2020. The research results show that one of the most crucial factors for the target group is the price of a product. If the price of a sustainable version was the same as the traditional one, all of respondents would choose eco-friendly packaging solution. There is a clear dependence between educational background, importance of eco-packaging and willingness to pay more for it. In general, the better educated consumer is, the more important eco-packaging is to them and the more they are willing to spend on it. Social media such as Facebook, Twitter, Instagram are clearly the preferred communication channel when it comes to sustainable cosmetic packaging. All of the other media and ways of promotion seem to be far less popular.
Keywords: Ecological consumer behaviour; cosmetic packaging; eco-packaging; Polish consumers; consumer attitude